(untitled) (CIPEEX, 2022)
THIS STUDY IS A LITERATURE REVIEW, THAT IS ABOUT THE FACTORS RESPONSIBLE FOR REFUSING IMMUNIZATIONAGAINST HPV, WHICH CORROBORATE A GREATER VULNERABILITY OF WOMEN’S HEALTH AND THE SPREAD OF THEVIRUS. THE ARTICLES’ SELECTION WAS BASED ON THE GUIDING QUESTION: €ŒWHAT ARE THE REASONS FOR THELACK OF ADHERENCE TO HPV VACCINATION AMONG ADOLESCENTS IN THE PREVENTION OF CERVICAL CANCER?€.THE DESCRIPTORS USED WERE VACCINATION, CERVIX AND HPV, WHICH WERE CHECKED THE DESCRITORESEM CINCIAS DA SAÚDE (DESCS), THE DATABASES USED WERE: BIBLIOTECA VIRTUAL EM SAÚDE BRASIL(BVS BRAZIL) AND GOOGLE SCHOLAR; WERE INCLUDED ARTICLES BETWEEN 2018 AND 2022, INPORTUGUESE (BRAZIL), FULL TEXTS AVAILABLE AND EXCLUDING LITERATURE REVIEWS. THE ARTICLES CHOSEDHAVE FOCUSED MAINLY ON: PATERNAL PREJUDGMENT RELATED TO THE VACCINE, SOCIOCULTURAL ISSUES,REGIONAL SOCIOECONOMIC DIFFERENCES, FEAR OF COLLATERAL EFFECTS, LACK OF KNOWLEDGE ABOUT THEVACCINE, THE VIRUS AND THE VACCINE CAMPAIGN AGAINST HPV, AS THE MAIN REASONS FOR LOW VACCINEADHERENCE. THUS, IT IS URGENT THAT MEASURES NEEDS TO BE TAKEN TO INCREASE VACCINATIONADHERENCE, THROUGH PUBLIC CAMPAIGNS IN SCHOOLS AND WORKPLACES, AND VISITS TO NEEDYCOMMUNITIES WITH THE AIM OF COVERING ALL AGES GROUPS AND SOCIOECONOMIC POSITIONS.